2008
DOI: 10.1002/mds.22097
|View full text |Cite
|
Sign up to set email alerts
|

Ten‐year rate of longitudinal change in neurocognitive and motor function in prediagnosis Huntington disease

Abstract: Longitudinal studies of neurocognitive function in prediagnosis Huntington disease (pre-HD) have been few, and duration of follow-up has been brief. In the current study, 155 individuals at-risk for HD completed a battery of cognitive and motor tasks at two study visits approximately 10 years apart. Participants were classified as: 1) at-risk, without the CAG expansion (normal controls, NC; n = 112), or 2) CAG expanded (CAG+; n = 43). To examine the rate of decline at different stages of the pre-HD period, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 21 publications
8
36
0
Order By: Relevance
“…The largest effect size was found for the SDMT, a task requiring coordination of visual scanning, working memory, fine motor speed, and concentration. These findings replicate those reported in the literature from at least six different studies7 8 10 11 13 15 and suggest that this task is highly sensitive and consistent for tracking decline in prodromal HD. Longitudinal change for every prodromal group was substantially different from the normal control group, suggesting the SDMT might serve as a sufficient outcome measure to detect alleviation of decline over time from an effective compound or intervention.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The largest effect size was found for the SDMT, a task requiring coordination of visual scanning, working memory, fine motor speed, and concentration. These findings replicate those reported in the literature from at least six different studies7 8 10 11 13 15 and suggest that this task is highly sensitive and consistent for tracking decline in prodromal HD. Longitudinal change for every prodromal group was substantially different from the normal control group, suggesting the SDMT might serve as a sufficient outcome measure to detect alleviation of decline over time from an effective compound or intervention.…”
Section: Discussionsupporting
confidence: 89%
“…Six of the studies reviewed (see table 1) showed significant changes over time using the Stroop Color Word Test8 10 14–16; the TMT,14–16 or other measures of reaction or movement time,13 14 all of which were found to have substantial effects in the current study. Some have interpreted this finding as reason to emphasise motor and psychomotor measures of HD as superior to other potential assessed outcomes 12.…”
Section: Discussionmentioning
confidence: 52%
“…Discrepancy due to overestimation on the sensitivity of measurements in cross-sectional studies suggests the importance of unbiased longitudinal studies for precise interpretation of the results and for determining possible clinical applications [1,6-8,37,38]. Unlike the cognitive behavioral assessment, non-invasive MRI provides an optimal quantitative tool for determining anatomical changes that may associate with the disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…9 years) [39] . Participants were stratified according to proximity to diagnosis because changes in behavior, cognition, emotional regulation, and motor function have been demonstrated prior to HD diagnosis [36,[40][41][42] , and being early in the course of illness has previously been suggested as a risk factor for suicide in HD.…”
Section: Methodsmentioning
confidence: 99%